Wellness, blaming and coping during a pandemic: an analysis of perceptions on reddit. Issue 3 (22nd July 2021) - Callaghan, Sarah; Drysdale, Maureen T.B.; Lee, Jessica
Abstract : Purpose: This study aims to examine Reddit posts regarding the COVID-19 pandemic from a subreddit dedicated to the campus community of a large, research-intensive Canadian University. The goal was to determine what users were sharing regarding their mental health, well-being, problems, coping strategies and perceptions about the health measures taken to prevent further spread. Design/methodology/approach: A total of 1, 096 paragraphs were analyzed using the qualitative methodology of thematic analysis. Findings: Many users expressed struggling with their mental health and well-being during the pandemic. Difficulties with online learning, finding paid study and affording the costs of living were also reported. Coping was largely conducted through online means and included sharing advice, emphasizing connectedness and communicating information. The mixed perceptions regarding health measures focused on responsibility and fairness, with many users blaming the university and public health units. Originality/value: This study contributes to the evolving understanding of how different populations are affected by the COVID-19 pandemic in Canada, specifically, university students. Implications for providing assistance to university students during the current pandemic and future waves are also discussed.